Live imaging of center of calcification formation during septum development in primary polyps of Acropora digitifera - Ohno, Yoshikazu; Takahashi, Anan; Tsutsumi, Motosuke; Kubota, Azusa; Iguchi, Akira; Iijima, Mariko; Mizusawa, Nanami; Nakamura, Takashi; Suzuki, Atsushi; Suzuki, Michio; Yasumoto, Jun; Watabe, Shugo; et al. (Frontiers in Marine Science, 2024)
Recent studies have revealed that stony corals create their extracellular skeletons via biologically controlled calcification, in which amorphous calcium carbonate (ACC), regarded as precursors of aragonite crystals, have been observed at nanoscale using electron microscopy. However, the exact mechanism by which ACC is generated, and how it contributes to skeletal growth in coral calcifying tissue, remains enigmatic. The septal skeleton of an individual polyp is composed of radially aligned plates extending upward from the aboral calcifying tissue. This structure includes microstructure known as the center of calcification (CoC). However, despite its importance, direct in vivo observation of septal growth has not been reported. Observations under transmitted illumination using polarized light microscopy on calcifying tissue of young Acropora digitifera revealed small crystals, a few micrometers in size, that accompany subtle movements and that emerge exclusively on the inner wall of the pocket in extracellular calcifying fluid (ECF). Crystal growth initiated from small, scattered crystals on a glass plate resembles this phenomenon observed in coral skeletons. Time-lapse photographs of 12 individuals in early primary polyp settlement revealed this process in three individuals, documenting 13 of these crystal events. This phenomenon occurred solely at the bases of subsequently formed septa. These crystals differ notably from fusiform crystals and from dumbbell-like or rod-like crystals growing individually. Upright two-photon microscopy captured movement of sub-micron-sized fluorescent calcein-accumulating particles, emphasizing their presence on the surface of the growing fronts of septa. Methodological advances that facilitate comprehensive in vivo observation of sub-micron-sized structures, calcein-accumulating particles to the skeleton, are needed to develop a more detailed understanding of coral skeletal growth.